IMPLEMENTASI MODEL EVALUASI FORMATIF-SUMATIF DALAM MENINGKATKAN PEMBELAJARAN SENI BUDAYA - Elpalina, Srimutia; Ambiyar, Ambiyar; Agustina, Agustina; Azis, Adek Cerah Kurnia (Gorga : Jurnal Seni Rupa, 2024)
AbstractThe learning of Arts and Culture plays a crucial role in shaping students' creativity, cultural understanding, and art appreciation. Despite its significance, Arts and Culture education faces several challenges, including insufficient school support, limited resources, technological challenges, and the availability of qualified teachers. Therefore, this research aims to explore the implementation of formative-summative evaluation models as an effort to enhance the quality of Arts and Culture education. The study employs a literature review method with four stages, involving the development of tools and equipment, compilation of bibliography, reading and noting research materials, and content and descriptive analysis. The results of the analysis reveal that the implementation of formative-summative evaluation models plays a central role in improving Arts and Culture education. Formative evaluation provides continuous feedback and identifies the need for improvement, while summative evaluation offers an overall picture of students' achievements. The application of this evaluation model involves the development of evaluation instruments, monitoring the learning process, adjusting teaching methods, providing feedback to students, identifying the need for improvement, and developing teaching and learning programs. The conclusions drawn from this study encompass the variation in the implementation of Arts and Culture education, the central role of teachers' creativity, and the positive impact of formative-summative evaluation models. Suggestions for further research involve a comparative study between schools, a focus on teacher qualifications, and further investigation into the influence of evaluation models on students' achievements and interest in the arts. Thus, the implementation of formative-summative evaluation models becomes an effective strategy in enhancing the quality of Arts and Culture education, contributing positively to students' creative development and cultural understanding.Keywords: formative-summative evaluation, arts and cultureAbstrakPembelajaran Seni Budaya memiliki peran krusial dalam membentuk kreativitas, pemahaman budaya, dan apresiasi seni siswa. Meskipun penting, pembelajaran Seni Budaya dihadapkan pada sejumlah tantangan, termasuk minimnya dukungan sekolah, keterbatasan sumber daya, tantangan teknologi, dan ketersediaan guru yang kompeten. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi implementasi model evaluasi formatif-sumatif sebagai upaya meningkatkan kualitas pembelajaran Seni Budaya. Studi ini menggunakan metode studi pustaka dengan empat tahap, melibatkan penyusunan alat dan perlengkapan, menyusun bibliografi, membaca dan mencatat bahan penelitian, serta analisis konten dan deskriptif. Hasil analisis mengungkapkan implementasi model evaluasi formatif-sumatif memainkan peran sentral dalam meningkatkan pembelajaran Seni Budaya. Evaluasi formatif memberikan umpan balik terus-menerus dan identifikasi kebutuhan perbaikan, sementara evaluasi sumatif memberikan gambaran keseluruhan tentang pencapaian siswa. Penerapan model evaluasi ini melibatkan pengembangan instrumen evaluasi, pemantauan proses pembelajaran, penyesuaian metode pengajaran, umpan balik kepada siswa, identifikasi kebutuhan perbaikan, dan pengembangan program belajar-mengajar. Kesimpulan dari studi ini mencakup variasi pelaksanaan pembelajaran Seni Budaya, peran sentral kreativitas guru, dan dampak positif model evaluasi formatif-sumatif. Saran untuk penelitian selanjutnya melibatkan studi komparatif antar sekolah, fokus pada kualifikasi guru, dan penelitian lebih lanjut tentang pengaruh model evaluasi terhadap prestasi dan minat siswa terhadap seni. Dengan demikian, penerapan model evaluasi formatif-sumatif menjadi strategi yang efektif dalam meningkatkan kualitas pembelajaran Seni Budaya, sekaligus memberikan kontribusi positif terhadap perkembangan kreativitas dan pemahaman budaya siswa.Kata Kunci: evaluasi formatif-sumatif, seni budaya Authors:Srimutia Elpalina : Universitas Negeri PadangAmbiyar : Universitas Negeri PadangAgustina : Universitas Negeri PadangAdek Cerah Kurnia Aziz : Universitas Negeri Medan References:Adlini, M. N., Dinda, A. H., Yulinda, S., Chotimah, O., & Merliyana, S. J. (2022). Metode Penelitian Kualitatif Studi Pustaka. Edumaspul: Jurnal Pendidikan, 6(1), 974“980.Astuti, K. S., Pamadhi, H., & Rini, Y. S. (2010). Pengembangan Model Evalasi Pembelajaran Seni Budaya SMP. Jurnal Kependidikan, 40(1), 87“98.Creswell, J. W. (2012). Educational Research: Planning, Conducting and Evaluating Qualitative and Qualitative Research. Boston: Pearson Education.Creswell, J. W. (2014). Research Design. California: SAGE.Fadli, M. R. (2021). Memahami Desain Metode Penelitian Kualitatif. Humanika, 21(1), 33“54.Fitrianti, L. (2018). Prinsip Kontinuitas dalam Evaluasi Proses Pembelajaran. Al-Ishlah: Jurnal Pendidikan, 10(1), 89“102.Fitzpatrick, J. L., Sanders, J. R., & Worthen, B. R. (2011). Program Evaluation Alternative Approaches And Practical Guidelines. Boston: Pearson Education.Hikmah, R. A., & Hakim, R. (2019). Pengembangan Modul Seni Budaya Berbasis Pendidikan Karakter Untuk Siswa Kelas X di SMK. Gorga: Jurnal Seni Rupa, 8(2), 417“423.James C. McDavid, Huse, I., & Hawthorn, L. L. (2019). Program Evaluation and Performance Measurement. London: SAGE Publishing.Linfield, K. J., & Posavac, E. J. (2019). Program Evaluation:Methods and Cases Studies. London: Routledge.Lubis, S. K. (2022). Evaluasi Kinerja Guru Seni Budaya Ditinjau dari Kesesuaian Latar Belakang Pendidikan Guru dengan Aspek Seni yang Diajarkan. Gorga: Jurnal Seni Rupa, 11(2), 394“401.Mardiah, M., & Syarifuddin, S. (2019). Model-model Evaluasi Pendidikan. Mitra Ash-Shibyan: Jurnal Pendidikan & Konseling, 2(1), 38“50.Mertens, D. M. (2015). Research and Evaluation in Education and Psychology. London: SAGE Publishing.Mertens, D. M., & Wilson, A. T. (2019). Program Evaluation Theory and Practice. London: The Guilford Press.Purwanto, M. N. (2020). Prinsip-prinsip dan Teknik Evaluasi Pengajaran. Bandung: Remaja Rosda Karya.Raharja, J. T., & Retnowati, T. H. (2013). Evaluasi Pelaksanaan Pembelajaran Seni Budaya SMA di Kabupaten Lombok Timur, NTB. Jurnal Pendidikan Dan Evaluasi Pendidikan, 17(2), 287“303.Selegi, S. F. (2017). Model Evaluasi Formatif-Sumatif Terhadap Motivasi Belajar Mahasiswa Pada Mata Kuliah Perencanaan Pengajaran Geografi. Seminar Nasional 20 Program Pascasarjana Universitas PGRI Palembang, 188“192.Stufflebeam, D. L. (1987). Meta Evaluation: An Overview. Evaluation and The Health Professions, 1(1), 17“43.Wulandari, N. S., & Hadi, H. (2023). Pembelajaran Seni Budaya di SMA Negeri 8 Padang. Journal On Teacher Education, 4(4), 157“164.